A Photoclick Hydrogel for Enhanced Single‐Cell Immunoblotting. (3rd March 2020) - Zhang, Ting; Li, Shanhe; Warden, Antony R.; Ghalandari, Behafarid; Li, Hongxia; Zhi, Xiao; Xie, Haiyang; Ding, Xianting
Abstract: Advances in single‐cell immunoblotting assays, which facilitate the exploration of cell‐to‐cell variation that affects biological systems from cancer development to stem cell biology, have attracted much attention. A tetrazole‐functionalized photoclick hydrogel is reported for single‐cell proteomic analysis. The gel serves as a molecular sieving matrix for sodium dodecyl sulfate–polyacrylamide gel electrophoresis and a protein immobilization scaffold for in‐gel immunoblotting. Upon a very short time (60 s) of long‐wavelength ultraviolet irradiation, it can effectively capture the electrophoretically separated proteins in the gel for the subsequent in situ antibody incubation. As a proof of concept, its performance is demonstrated in profiling cell‐to‐cell variations of P‐glycoprotein expression in GES‐1/MGC803 cell lines treated with different drugs. Combined with single‐cell immunoblotting method, employing this photoactive gel enables the monitoring simultaneously in ≈2000 individual cells of subtle protein expression level changes that may be concealed using conventional techniques. The proposed gel has the advantages of excellent electrophoretic separation ability, high protein photoimmobilization efficiency, low autofluorescence, and it can be used as a promising photoactive polyacrylamide gel for in‐gel/in situ capillary and microfluidic immunoblotting assays, especially for developing novel single cell immunoblotting methods. Abstract : A tetrazole‐functionalized photoclick hydrogel is developed for enhanced singe‐cell immunoblotting. With its excellent electrophoretic separation ability, high protein photoimmobilization efficiency, and low autofluorescence, the hydrogel serves as a molecular sieving matrix for gel electrophoresis and a protein immobilization scaffold for in‐gel immunoblotting, and is promising for in‐gel/in‐situ capillary and microfluidic immunoblotting assays.